Labour market effects of supply chain bottlenecks - Markus Hummel; Christian Hutter; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
During the COVID-19 pandemic there were supply chain bottlenecks all over the world with regard to raw materials and intermediate products. In this article, we examine how these constraints affected labour market development. For an empirical panel analysis, we combine survey data and administrative labour market data for economic sectors in Germany. We find effects on unemployment that are noticeable but still relatively limited. The effect on short-time work, on the other hand, is revealed to be considerable. Whilst short-time work is traditionally imposed where there are slumps in demand, our results show that it is also used in the case of adverse supply shocks. While inflation is rising, this explains why the Phillips curve does not shift outward. – – Während der COVID-19-Pandemie kam es weltweit zu Lieferkettenengpässen bei Rohstoffen und Zwischenprodukten. In diesem Artikel untersuchen wir, wie sich diese Einschränkungen auf die Arbeitsmarktentwicklung ausgewirkt haben. Für eine empirische Panelanalyse kombinieren wir Befragungsdaten und administrative Arbeitsmarktdaten für Wirtschaftsbereiche in Deutschland. Wir finden spürbare, aber noch relativ begrenzte Auswirkungen auf die Arbeitslosigkeit. Die Auswirkung auf die Kurzarbeit erweist sich dagegen als erheblich. Während Kurzarbeit traditionell bei Nachfrageeinbrüchen verhängt wird, zeigen unsere Ergebnisse, dass sie auch bei negativen Angebotsschocks zum Einsatz kommt. Bei steigender Inflation erklärt dies auch, warum sich die Phillips-Kurve nicht nach außen verschiebt.
Keywords: C23; E24; E31; J63; J64; 330; material shortages; supply chain; labour market; COVID-19 crisis; short-time work